Causes and impacts of land degradation and desrtification: case study of the Republic of Kazakhstan (Journal of Geography and Environmental Management, 2017)
The article considers the сauses and impacts of land degradation and desrtification: case study of the Republic of Kazakhstan. The problem of desertification is a serious threat to the well-being of humanity. In addition to the environmental violations, desertification causes a variety of negative social and economic consequences. Soil degradation is always accompanied by the systematic use by the human. However, over the last decades this process has accelerated; just at a time when population growth and forecast of further growth necessitate sharply increase the food production. It is estimated that annually about 50-70 thousand sq. km of fertile land becomes unusable.                As a result of the research authors identified the most vulnerable to desertification agricultural land and proposed measures for the prevention of desertification. Some of the key measures are the forest plantation and using of pasture ecosystems through their conservation and sustainable use for restoring the functional integrity of steppe ecosystems.
Keywords: desertification; land degradation; pasture; drought; ecosystems